Effect Of Supplementation Of Vitamin E And Selenium On Serum Enzyme Profiles In Hallikar Cattle During Different Seasons - Kalmath, G. P.; Swamy, M. Narayana; Yathiraj, S; Krishnaswamy, A.; Nagaraj, C. S.; Isloor , Srikrishna (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
A study was carried out to assess the influence of summer stress and effect of supplementation of vitamin E and selenium during different season on serum enzyme activities, i.e., aspartate aminotransferase (AST), alanine aminotransferase (ALT) and alkaline phosphatase (ALP) in Hallikar cattle. In the control group, activities of AST, ALT and ALP were significantly (P
Keywords: Summer stress; antioxidants; ALT; AST; ALP